PERLINDUNGAN HAK PEREMPUAN ATAS PENGEMBALIAN MAHAR DALAM PERCERAIAN PADA MASYARAKAT ADAT BUGIS-MAKASSAR: Protection Of Women’s Rights To Return Of Dowry In Bugis-Makassar Customary Divorce - Syarifah Prasya Andienda; Harto (Reformasi Hukum Trisakti, 2026)
Marriage in Bugis-Makassar customary society is understood not only as a religious bond but also as a social event embedded with customary values, particularly concerning mahar (sompa) and uang panaik (doi panaik). Mahar is a mandatory requirement in Islamic marriage and normatively becomes the absolute right of the wife from the moment the marriage contract is concluded, while uang panaik serves as a symbol of customary respect toward the bride’s family. The different legal positions and functions of these two concepts often lead to disputes in cases of divorce, especially regarding claims for the return of mahar. This study examines the perspective of the Compilation of Islamic Law on the protection of women’s rights in Decision Number 63/Pdt.G/2021/PA.Mks. This research is a descriptive normative legal study using secondary data analyzed qualitatively, with conclusions drawn through deductive reasoning. The results show that Article 32 of the KHI affirms mahar as the absolute right of the wife; however, in Decision Number 63/Pdt.G/2021/PA.Mks., the judges still accommodated customary values by granting the partial return of mahar. Therefore, it can be concluded that the protection of women’s rights has not been fully consistent with the provisions of the KHI.